Effects of Gender and Age Interaction on Sense of Coherence and Subjective Well-Being of Senior High School Students in Northern Ghana - Edmond Kwesi Agormedah; Francis Ankomah; Medina Srem-Sai; Regina Mawusi Nugba; Frank Quansah; John Elvis Hagan; Orkan Okan; Kevin Dadaczynski; Thomas Schack (MDPI AG, 2024)
Though several studies have established the effect of gender and age on the sense of coherence (SoC) and subjective well-being (SWB) among diverse populations, findings have been varied and inconclusive. These inconsistencies have been attributed to the differences in sample characteristics, methodological and cultural disparities. Thus, the present study assessed the following: (1) gender and age effect on SoC, (2) gender and age effect on SWB, and (3) moderating roles of gender and age in the link between SoC and SWB. Through a stratified sampling technique, 724 selected high school students from secondary schools in Northern Ghana completed the World Health Organization-5 Well-Being and Sense of Coherence instruments. The results showed that female students exhibited higher levels of SoC compared to their male counterparts. Whereas younger male and female students showed no significant difference in SWB levels, older female students, compared to older males, exhibited high levels of SWB. Age significantly moderated the relationship between SoC and SWB. With the same level of SoC, younger students were more likely to exhibit higher SWB compared to older ones. The findings call for sustainable gender- and age-based interventions because students subjectively develop SoC mechanisms for improving their well-being.